IoT-Based Monitoring System for Diagnosing Adverse Drug Reactions and Enhancing Drug Compliance in TB Patients - Sharma, Anshu; Sharma, Anurag; Malhotra, Rahul (Computer Assisted Methods in Engineering and Science, 2023)
Health plays a prime role for day-to-day working. IoT provides physicians and patients with advanced medical resources, solutions, services, advantages etc. The goal behind the internet of things (IoT) is to have IoT devices that self-report in real-time. This project aims to develop a system that provides live-body temperature, cough detection, pulse rate and other health criteria such as weight loss, chest pain detection, blood sugar level, HB-WBC-RBC (hemoglobin, white blood cell, red blood cell) level, etc. NodeMcu, an open-source firmware, is used for wireless data transmission on an IoT platform. The data is stored on a web server so it can be accessed by both the physician and patient to provide the information about the patient’s condition and help the physician to diagnose TB for the patient. The data of 50 patients have been collected for analysis and reviewed in detail in the result and analysis section.